Team planning for project managers and business analysts - Levitt, Gail (ESI International project management series., 2013)
Supplying busy project professionals with time-tested tips and templates for developing teams efficiently and effectively, Team Planning for Project Managers and Business Analysts provides the planning materials required to increase team collaboration and productivity in a global workplace. This comprehensive resource offers insights and access to critical resources and tools to create, propose, execute, and evaluate team development plans. Dr. Levitt's insights will enable readers to transform their visions, mission statements, goals, and deliverables into actionable plans for their teams. Te.